2004
DOI: 10.2169/internalmedicine.43.1115
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Microparticles and the Diagnosis of the Vasculitides

Abstract: Recently there has been considerable interest in a novel surrogate marker of endothelial injury, endothelial microparticles (EMP), in a number of diseases characterised by endothelial injury. This review examines the data relating to EMP in human disease states, and examines the potential for EMP to provide a window onto the activated endothelium in primary systemic vasculitides. The utility of EMP for the diagnosis and monitoring of active vasculitis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Although not a routine investigative procedure, the recently developed measurements of circulating endothelial microparticles and circulating endothelial cells may prove helpful in demonstrating the presence of active vasculitic disease as well as throwing light on the mechanisms involved [5662]. Furthermore, measurement of circulating endothelial progenitor cells may be helpful in pointing to evidence of a repair process being under way in the recovery phase of disease [61, 63].…”
Section: Polyarteritis Nodosamentioning
confidence: 99%
“…Although not a routine investigative procedure, the recently developed measurements of circulating endothelial microparticles and circulating endothelial cells may prove helpful in demonstrating the presence of active vasculitic disease as well as throwing light on the mechanisms involved [5662]. Furthermore, measurement of circulating endothelial progenitor cells may be helpful in pointing to evidence of a repair process being under way in the recovery phase of disease [61, 63].…”
Section: Polyarteritis Nodosamentioning
confidence: 99%
“…Studies of endothelial function have demonstrated profound impairment during active disease which does not normalize in remission, suggesting both a vascular effect of incomplete disease control and a risk factor for later cardiovascular events 63 . Circulating endothelial cells, endothelial microparticles and other endothelial markers, such as von Willebrand factor, are elevated during active vasculitis and have potential as indicators of vascular health 64–66 …”
Section: Future Therapies Of Vasculitismentioning
confidence: 99%
“…For example, the abundance of endothelial and platelet microvesicles was indicated to correlate more specifically with thrombotic manifestations of antiphospholipid syndrome than antiphospholipid antibody levels alone and might thus provide an additional information for defining the disease [7,8,23]. Also detection of microvesicles could be used in conjunction with perceived gold-standards (tissue biopsy, angiography) for the diagnosis of active vasculitis [24] and for assessing the activity of rheumatoid arthritis [25].…”
Section: Introductionmentioning
confidence: 99%